FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN RENDAHNYA KUNJUNGAN LANSIA PADA PGROGRAM POSYANDU LANSIA DI PUSKESMAS PADANG BULAN - Jaka Berlin Sinuraya; Risky Ramadani; Dameria Dameria (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2019)
The elderly Posyandu is a community service program intended for the elderly population that focuses on health services but also includes other services according to the needs of the age range aimed at developing the potential and ensuring the welfare of the elderly. There are three aspects that influence the low level of lansian visits to the posyandu for the elderly, namely knowledge, attitudes, and the role of health workers. This research is an analytic survey with cross sectional research design to find out factors related to the low elderly visits to the elderly posyandu program at the Puskesmas Padang Bulan 2018. Data collection was carried out using a questionnaire, data analysis was carried out by univariate and bivariate tests. Based on the results of this study, that there is a relationship between the knowledge of the elderly, attitudes and the role of health workers with the low visits to the elderly posyandu program where the results of the calculation of elderly knowledge are X²count 13.292> X²table 5.99 and p value = 0.001, the results of the calculation of elderly attitudes namely X²count 36,458> X²table 5,99 and the value of p value = 0,000, and the results of the calculation of the role of health workers that is X²test63,343> X²table3,841 and p value = 0,000. The conclusion of this study is, there is a relationship between elderly knowledge, attitudes, the role of health workers with low visits to the elderly Posyandu program. Researchers expect the role of health workers to provide education to the elderly so that the elderly like to attend the Posyandu for the elderly.